IMPLEMENTASI KURIKULUM MADRASAH DINIYAH DALAM MENUMBUHKAN SIKAP RELIGIUS SISWA DI SMPN 1 PETERONGAN JOMBANG - Alvira Rachmadani (JOURNAL SAINS STUDENT RESEARCH, 2024)
The Madrasah Diniyah curriculum is an educational program provided to teach students. With this program, students carry out various learning activities, resulting in changes and developments in student behavior, in accordance with educational and learning goals. One real solution for educating students with noble morals, the Jombang Regency Government is currently carrying out innovations in the field of education by using Madrasah Diniyah as a local religious curriculum.The focus of this research is to find out how the Madrasah Diniyah curriculum is implemented at SMPN 1 Peterongan Jombang, what the religious attitudes of students at SMPN 1 Peterongan Jombang are, and how the Madrasah Diniyah curriculum can be implemented towards students' religious attitudes.This research method uses a qualitative approach. This type of research is case study research. As seen from the data collection techniques in this research using observation, interview and documentation techniques. Meanwhile, the data analysis techniques used are data reduction, data presentation, and drawing conclusions.The results of research carried out by researchers implementing the Madrasah Diniyah curriculum at SMPN 1 Peterongan Jombang include teaching skills for both fardhu and sunnah prayers, honing reading and writing of the Qur'an, insight into prayer and worship, as well as teaching about rote memorization, including memorizing letters. in the Qur'an and daily prayers. The religious attitude of students at SMPN 1 SMPN 1 Peterongan Jombang is not only committed to God's commands and prohibitions, but they also apply good manners in their behavior. Students are active in following religion and are enthusiastic about learning daily prayers and memorizing short letters. The implementation of the Madrasah Diniyah curriculum in cultivating students' religious attitudes at SMPN 1 Peterongan Jombang takes the form of; teachers provide religious knowledge instruction such as students are required to read the Koran before the start of lessons, students are taught to practice religious skills such as practicing obligatory and sunnah prayers, memorizing short letters and daily prayers. So that from this, students have a religious attitude such as being committed to God's commands and prohibitions, practicing good manners, being active in participating in religious activities and being enthusiastic about learning daily prayers and memorizing short letters.